Effect of aquatic plants and associate microhabitats on early life stages of fish - Ferrer, Orlando; Dibble, Eric (Ciencia, 1970)
We examined the effect of aquatic plants and some associate microhabitats on abundance of early life stages of fish in a backwater cove of Aliceville Lake, a reservoir on the Tennesse-Tombigbee Waterway, located on the Alabama-Mississippi border. Abundance of early life stages of fish, along with physicochemical and plant habitat variables were measured from March to August 1998. Biological samples were collected with modified Quatrefoil light traps. Principal component analysis, detrended correspondence analysis, and multiple linear regression were used to detect associations of early life stages of fish with physicochemical and habitat structure variables. We collected 1,388 fish representing 12 genera and 9 families. Evidence from our study demonstrated that aquatic plants can create habitat availability in ways different than structural complexity. We identified different physicochemical structures in the studied cove owing to different levels of plant coverage. Our results suggest that levels of plant coverage of up to 25% create physicochemical conditions that can positively influence habitat availability for spawning and early life stages of fish. Low levels of plant coverage could increase temperature and dissolved oxygen during early spring, triggering fish early spawning. The identification of appropriate levels at which aquatic vegetation provides a good-quality habitat for early life stages of fish is important for successful fisheries and aquatic plant management.